The Role of Physiological Afferent Nerve Activity during In Vivo Maturation of the Calyx of Held Synapse - Erazo-Fischer, Emilio (J Neurosci, 2007)
We studied how afferent nerve activity affects the in vivo maturation of a fast glutamatergic CNS synapse, the calyx of Held. To address this question, we exploited the distinct presynaptic Ca(2+) channel subtypes governing transmitter release at the cochlear inner hair cell (IHC)–spiral neuron synaptic junction compared with those at higher synapses along the auditory pathways. We characterized the functional properties of calyx synapses in wild type (wt) compared with those developing in Ca(V)1.3 subunit-deficient (Ca(V)1.3(−/−)) mice. Ca(V)1.3(−/−) mice are deaf because of an absence of glutamate release from IHC, which results in a complete lack of cochlea-driven nerve activity. Presynaptic Ca(2+) channel properties, Ca(2+) dependence of exocytosis, number of readily releasable quanta, and AMPA mEPSCs were unchanged in postnatal day 14 (P14) to P17 calyx synapses of Ca(V)1.3(−/−) mice. However, synaptic strength was augmented because presynaptic action potentials were broader, leading to increased quantal release, consistent with lower paired-pulse ratios and stronger depression during repetitive synaptic stimulation. Furthermore, asynchronous release after trains was elevated presumably because of higher residual Ca(2+) accumulating in the presynaptic terminals. Finally, we measured larger NMDA EPSCs with higher sensitivity to the NR2B subunit-specific antagonist ifenprodil in P14–P17 synapses of Ca(V)1.3(−/−) compared with wt mice. These results suggest that auditory activity is required for the adjustment of synaptic strength as well as for the downregulation of synaptic NMDA receptors during postnatal development of the calyx of Held. In contrast, properties of the presynaptic release machinery and postsynaptic AMPA receptors are unaffected by chronic changes in the level of afferent activity at this synapse.